Best practice in primary care pathology: review 12. Issue 4 (30th March 2010) - Smellie, W S A; McNulty, C A M; Collinson, P O; Shaw, N; Bowley, R
Abstract : This twelfth best practice review examines four series of common primary care questions in laboratory medicine: (i) antiepileptic drug monitoring; (ii) infectious diarrhoea; (iii) methicillin resistant Staphylococcus aureus ; and (iv) brain natriuretic peptide. The review is presented in question–answer format, referenced for each question series. The recommendations represent a précis of guidance found using a standardised literature search of national and international guidance notes, consensus statements, health policy documents and evidence-based medicine reviews, supplemented by MEDLINE EMBASE searches to identify relevant primary research documents. They are not standards but form a guide to be set in the clinical context. Most are consensus rather than evidence-based. They will be updated periodically to take account of new information.